2016
DOI: 10.17795/bhs-38629
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Hospitals Affiliated to Mashhad University of Medical Sciences Using the Pabon Lasso Model: A Six-Year-Trend Study

Abstract: Background: Nowadays, productivity and efficiency are considered a culture and a perspective in both life and work environments. This is the starting point of human development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In the DEA model, the performance score varies from 1 in the Universities of Ardebil, Bojnourd, Bushehr, Dezful, Gilan, Gonabad, and Kordestan to 0.371 in Kashan University. A considerable part of the studies took place inside the country in the case of efficiency of health systems where focus was made on the hospitals [5,7,[66][67][68][69][70][71][72] and this has indicated different degrees of inefficiency in the sector of hospital services of the country. Of the studies achieved on a comprehensive scale in regard to the evaluation of performance of the health system in Iran in the case of efficiency of all the scopes (education, research, health, and treatment), reference can be made to the study by Rashdian and his colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the DEA model, the performance score varies from 1 in the Universities of Ardebil, Bojnourd, Bushehr, Dezful, Gilan, Gonabad, and Kordestan to 0.371 in Kashan University. A considerable part of the studies took place inside the country in the case of efficiency of health systems where focus was made on the hospitals [5,7,[66][67][68][69][70][71][72] and this has indicated different degrees of inefficiency in the sector of hospital services of the country. Of the studies achieved on a comprehensive scale in regard to the evaluation of performance of the health system in Iran in the case of efficiency of all the scopes (education, research, health, and treatment), reference can be made to the study by Rashdian and his colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…There is an endless interest in the design and application of a combination of methods and frameworks for measuring the performance of these organizations [5]. With regard to the obvious relationship between the definition of technical efficiency and the definition of health systems performance, efficiency has been expressed as the most important and prevalent mechanics and key for measurement and evaluation of the performance [1,6,7]. The first effort made for evaluating the performance of health systems by applying the concept of efficiency was made by WHO in 2000; having evaluated the efficiency of health systems in 191 countries of the world [8].…”
Section: Introductionmentioning
confidence: 99%
“…30 Finally, a previous study on the Affiliated Hospital of the Medical College of Iran showed that the average ALOS was 4.1, 31 3.2 32 and 4.1-4.6 days. 33 In 2018, ALOS in many APEC countries is 4-10 days, 34 China's general hospitals have ALOS of 8.5 days, while Beijing's 10 general public hospitals have ALOS of 11.3 days, and the 8 hospitals with a more comprehensive nature have an ALOS of 7.31 days.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Since then, this model has been used numerous times to assess hospital performances. [2,[12][13][14][15][16][17][18][19] The Pabón-Lasso model is a graphical presentation of hospital performance in which vertical and horizontal lines are set at the average values of BOR and BTR, respectively. These lines form axes that divide the graph into four sectors representing different productivity levels based on these commonly used performance indicators.…”
Section: Introductionmentioning
confidence: 99%